Cost-effective approach for structural evolution of Si-based multicomponent for Li-ion battery anodes. Issue 5 (11th January 2017) - Hong, Dongki; Ryu, Jaegeon; Shin, Sunghee; Park, Soojin
Abstract : Al2 O3 passivated porous Si particles with novel electrochemical properties were successfully demonstrated as outstanding anodes. Abstract : Silicon-based composite materials have been attracting significant attention because they offer an effective strategy for resolving the drawbacks of Si anodes, such as mechanical failure caused by significant volume changes and the resulting unstable interface. These drawbacks significantly affect the electrochemical properties of Si anodes and thereby inhibit their commercialization. Coupling Si anodes with inactive Al2 O3 materials is one possible way of addressing these issues. In this study, we developed Si-based multicomponent anode materials comprising a multiscale porous silicon framework uniformly passivated with thin Al2 O3 layers. This was achieved using a cost-effective, simple process of selective etching and wet oxidation. We found that the structural properties depended strongly on the Al residue in the core, which later generated asymmetries in the structure and the effective passivation layers. Our novel materials exhibited an excellent battery performance because of the structural robustness conferred by the Al/Al2 O3 core support combined with the mechanical stability of the Al2 O3 layers. The outermost protecting layers were also shown to enhance Li-ion diffusion through the Li-ion-conducting layers; this stabilized the solid–electrolyte-interphase layers. The wet oxidized Al–Si alloy (ASWO) exhibited an improved cycling performance with 81.9% capacity retention after 500 cycles at 0.2C in a Li half cell. In addition, a full cell using an ASWO-natural graphite (NG) anode and a lithium cobalt oxide (LCO) cathode exhibited excellent cycling performance with 75.3% capacity retention after 200 cycles at 1C.